Earnings Announcements, Information Asymmetry, and Timing of Debt Offerings - Kerr, Jon N.; Ozel, N. Bugra (The Accounting Review, 2015)
ABSTRACT We empirically examine the joint predictions of the pecking order theory and the theory of time-varying asymmetric information regarding the timing of security offerings around information disclosures. We analyze loan originations and bond offerings around earnings announcements and compare them against equity offerings. In support of the theories' predictions, we find a positive association between the information sensitivity of securities and the likelihood of their issuance after earnings announcements. In particular, we find that clustering after earnings announcements is weakest in loan originations, stronger in bond offerings, and strongest in equity offerings. Also consistent with the theories, we find that the size of news in earnings announcements matters in the timing decision. We find weak evidence regarding the theories' implication that the direction of news in the announcement plays a role in the timing decision. We test and find that this latter result is partly attributable to potential costs associated with the omission of material negative information, such as litigation risk. JEL Classifications: D82; G14; G39; M41.